Praktyka tworzenia edukacyjnej wspólnoty – o edukacyjnej codzienności w kontekście jawnych i ukrytych wzorów kultury szkolnej - Sadowska, Sławomira (Wydawnictwo Naukowe UAM, 2015)
The constitutive feature of the modern school is orientation towards a person’s attitude (moral, social), personal and civilizational competence, and the values of defining the quality of people’s lives. The processes that become more important are the ones that prepare the individual for living in a socially and culturally diverse world and equip him/her with the skills allowing the exploration and experience of the meaning of the world of disabled people, tolerate dissimilarity and otherness, consent to the existence of persons with disabilities on an equal footing. As a result of these processes, students should distance themselves from the concept of alienation and hostility, should treat dissimilarity and otherness not in terms of risks but rather as something stimulating, supportive for the understanding of the human being and the world. The article reflects on the possibilities of public and integration schools for the delivery of these objectives. The area of analysis reveals the explicit and implicit patterns of school culture. The direction of the analyses reinforces the reflection on what is possible, political and daily practice.
The Practice of Creating an Educational Community – Everyday Education in the Context of Explicit and Implicit Patterns of School Culture
Keywords: school culture; community education; disability; integration